Impacts of planned quality change in physical workplace on employees' behaviour: a quasi-experiment. (3rd April 2022) - Ng, Stephen C. H.; Lau, Victor P. L.; He, Yuanqiong
Abstract : The literature has long suggested that the prime objective of planned change is to establish desired employee behaviour. However, the planned operational change's behavioural effect is nevertheless ambiguous in the literature. This study aims to bridge this gap and evaluate how a planned change at the operational level affects employee behaviour. As the scope of planned operational change is usually broad, we focus on studying the change in a physical workplace: 5S via a quasi-experiment. 5S is different from other planned changes such as TQM which requests a wide range of synchronised changes in the organisation. We conceptualise 5S as a change intervention aimed at regulating the physical workplace and nurturing desired employee behaviour. We examine the difference in perceived self-discipline between 99 pairs of operators from a treatment group and a control group formed by propensity score matching (PSM). After controlling two organisational support factors, the quasi-experiment result reveals that the increase in the treatment group's perceived self-discipline is significantly more massive than that of the control group. This study sets the stage for advancing research in planned operational change and opens an avenue for empirical investigation of operations management.